Curricula development in library science : a nation-wide core curriculum? / Ursula Georgy - Georgy, Ursula (2011)
Curriculum development is a time-consuming process and often interminable. Pursuing the idea of creation a nationwide core curriculum is one opportunity to develop a curriculum in library and information science (LIS). It can be supposed that a project like this can be the initial point stimulating and encouraging the widest possible discussion between different educational environments. Furthermore, it can strengthen the cooperation and collaboration between LIS educational institutions, 'the European project in 2005 has shown that there are more differences than similarities in the European LIS curriculum [Kajberg, L.0rring 2005]. But nonetheless the discussion about a core curriculum can be an opportunity and a challenge for universities, students and libraries / companies in many countries around the world. The key question is how to create reliable framework conditions that will speed up the procedure of developing a nation-wide common core curriculum? A second question is: what consequences to be drawn if it appears that there are only a few similarities in the curricula or the universities show little willingness to modify the curricula in a study reform process?. The European project will be reflected and the own long time experience in curriculum development will be contributed. A nation-wide or international core curriculum seems to be inappropriate for a direct transfer into the participating institutes or universities. But finally, it would ensure greater cooperation and collaboration, thereby multiplying the chances of long-term cooperations and enhancing reputation of universities among employers, e.g. libraries. Keywords: Curriculum; Core curriculum; Study reform; Library and Information Science (US); LIS educational institutions; Bologna process